CO2 Utilization and Market Size Projection for CO2-treated Construction Materials - Sick, Volker; Stokes, Gerald; Mason, Fred C. (Frontiers in Climate, 2022)
Achieving a net climate benefit requires that captured CO2 (from stack emissions, directly from air or any other source) does not return to the atmosphere. There are several negative-emissions technologies that will meet this criterion. First, underground storage, possibly coupled with mineralization underground, creates essentially permanent removal. Second, CO2 can be mineralized above ground into benign solid materials that can be left in the environment. Third, construction materials such as concrete, aggregates, and wall boards can be made with the use of CO2. From a climate point of view the lifetime of those materials can be considered permanent. While structures (buildings, roads, etc) will not last permanently, the mineralized CO2 in the underlying raw materials will. The latter negative emissions technology category has the added benefit of creating revenue from the sale of the products and thus providing financial incentives for deployment. The potential CO2 utilization amount and market size for mineral-based construction materials is projected from today to 2050 and is discussed in context of the total addressable market for respective products. A range of scenarios for growth are considered and discussed. CO2 utilization at several gigatons per year is projected with a market valuation reaching $1 trillion/year by 2050.